Prevalent Occurrence of Plasmodium Falciparum Malaria in Pakistan - Abdul Qader Khan, Sumbal Hussain, Nazish Babar, Abdul Samad, Noor Badshah, Sadir Zaman (Pakistan Journal of Medical & Health Sciences, 2023)
Background: In Pakistan Plasmodium falciparum has been on the rise over the last few decades. Objective: This study primarily focused upon finding out the prevalent occurrence of malaria caused by Plasmodium falciparum in Pakistan. Methodology: This research analyzed different variables related to the respondents (n=209) of the study. The variables included age, occupation, education, patient’s visit to the hospital, transmission of malaria, prior treatment of the patient (if any), usage of long lasting insecticidal nets (LLINs), hygienic/unhygienic conditions and insecticidal spraying. Investigative analysis was purely based upon a questionnaire followed by the fundamental microscopic and polymerase chain reaction (PCR) for assessing the disease index. Results: The results indicated that out of 209 respondents of the study, 100% tested positive for malaria whereas, only 179 (85.6%) cases were confirmed via PCR analysis and were chosen for further investigations. Males (67%) were found to be more prone for malarial infection. Respondents in the age group of 26 to 35 years were the most (43.5%) vulnerable to this infection. 32.9% laborers, as compared to any other occupation affected by plasmodium. About 77.6% of people had already been infected by malaria and were treated, but only 14.5 % people visited the hospital. In addition to this, merely 12.2% respondents had used LLINs and 2.23% of them had utilized insecticidal spray. Conclusion: Lack of awareness, selfmedication, unhygienic environment, unemployment, and political instability contributed to malarial transmissions. Keywords: Malaria, Plasmodium falciparum, Pakistan, Microscopy, PCR.